1982
DOI: 10.1046/j.1468-2982.1982.0202083.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hypoxia: The Turning-Point in the Genesis of the Migraine Attack?

Abstract: The hypothesis postulates that a brief episode of focal cerebral hypoxia occurs in every attack of migraine. Clinical biochemical and technical (EEG and CT scans) evidence is summarized suggesting that cerebral hypoxia is seen as the turning-point in the pathogenesis of the attack. It may be provoked by different mechanisms in different patients; the potential role of decreased oxygen supply and of increased oxygen need are reviewed and excess sympathetic drive is considered a potential key mechanism in a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 167 publications
(158 reference statements)
1
40
0
Order By: Relevance
“…Interestingly, if the latter mechanism does indeed prove to be relevant to the acute antimigraine effects of triptans, the corollary might provide a clue as to the nature of the hitherto elusive migraine trigger. In this respect, it is tempting to speculate that cerebral focal hypo-oxygenation may be involved, as suggested previously (Amery, 1982). The availability of analytically powerful techniques such as blood oxygen level-dependent functional magnetic resonance imaging (Thompson et al, 2003) may encourage future investigation in this direction.…”
mentioning
confidence: 87%
“…Interestingly, if the latter mechanism does indeed prove to be relevant to the acute antimigraine effects of triptans, the corollary might provide a clue as to the nature of the hitherto elusive migraine trigger. In this respect, it is tempting to speculate that cerebral focal hypo-oxygenation may be involved, as suggested previously (Amery, 1982). The availability of analytically powerful techniques such as blood oxygen level-dependent functional magnetic resonance imaging (Thompson et al, 2003) may encourage future investigation in this direction.…”
mentioning
confidence: 87%
“…The vessels ultimately dilate, possibly assisted by the presence of vasodilator metabolites accumulated during the constrictor phase or perhaps by a reflex inhibition of the constrictor drive. In a recent review relating brain hypoxia to migraine, Amery 9 asserts that excess sympathetic drive is a potential key mechanism in a majority of migraineurs. Nielsen et al 4 established that sympathetic nerves make contact with the cerebral vessels while Falck et al 5 demonstrated histo chemically that adrenergic vasoconstrictor fibers are distributed to the larger cerebral vessels.…”
Section: Introductionmentioning
confidence: 99%
“…1 According to this hypothesis, a short episode of focal cerebral hypoxia may be the turning point in the migraine attack. A defensive strategy, with simple analgesics or ergot preparations, complements more offensive methods which -in keeping with varying theories about the pathogenesis of migraine -imply the use of 5-HT blockers, sympatholytics, ß-blockers, "anti-aminics" and sedative agents.…”
Section: Introductionmentioning
confidence: 99%